Genome-wide association study for resistance to Pseudomonas syringae pv. garcae in Coffea arabica - Ariyoshi, Caroline; Sant’ana, Gustavo César; Felicio, Mariane Silva; Sera, Gustavo Hiroshi; Nogueira, Livia Maria; Rodrigues, Lucas Mateus Rivero; Ferreira, Rafaelle Vecchia; da Silva, Bruna Silvestre Rodrigues; Resende, Mário Lúcio Vilela de; Destéfano, Suzete Aparecida Lanza; Domingues, Douglas Silva; Pereira, Luiz Filipe Protasio (Frontiers in Plant Science, 2022)
Bacteria halo blight (BHB), a coffee plant disease caused by Pseudomonas syringae pv. garcae, has been gaining importance in producing mountain regions and mild temperatures areas as well as in coffee nurseries. Most Coffea arabica cultivars are susceptible to this disease. In contrast, a great source of genetic diversity and resistance to BHB are found in C. arabica Ethiopian accessions. Aiming to identify alleles associated with resistance to BHB and the influence of these genomic regions during the domestication of C. arabica, we conducted an analysis of population structure and a Genome-Wide Association Study (GWAS). For this, we used genotyping by sequencing (GBS) and phenotyping for resistance to BHB of a panel with 120 C. arabica Ethiopian accessions from a historical FAO collection, 11 C. arabica cultivars, and the BA-10 genotype. Population structure analysis based on single-nucleotide polymorphisms (SNPs) markers showed that the 132 accessions are divided into 4 clusters. These clusters showed singularities in relation to the domestication level of the accessions. In addition, we identified a higher frequency of Ethiopian accessions resistant to BHB in the cluster with a higher domestication level. GWAS, using the single-locus model MLM and the multi-locus models mrMLM, FASTmrMLM, FASTmrEMMA, and ISIS EM-BLASSO, identified 13 alleles associated with resistance to BHB. Among these alleles, the four with the highest values of association for resistance to BHB are linked to g000 (Chr_0_434_435) and g010741 genes, which are predicted to encode a serine/threonine-kinase protein and a nucleotide binding site leucine-rich repeat (NBS-LRR), respectively. These genes displayed a similar transcriptional downregulation profile in a C. arabica susceptible cultivar and in a C. arabica cultivar with quantitative resistance, when infected with P. syringae pv. garcae. However, peaks of upregulation were observed in a C. arabica cultivar with qualitative resistance, for both genes. Our results provide SNPs that can be used in Marker Assisted Selection (MAS) and expand our understanding about the complex genetic control of the resistance to BHB in C. arabica. In addition, the findings contribute to increasing understanding of the C. arabica domestication history.